Effect of spent yeast fortification on physical parameters, volatiles and sensorial characteristics of home-made bread - Martins, Zita Emanuela (2015)
The impact of bread fortification with dry spent yeast from brewing industry on physical, chemical and sensorial characteristics of home-made bread was evaluated with the goal of increasing its β-glucan content. A serving of 50 g of bread fortified with dry spent yeast increased β-glucan intake from 65 to 125 mg, which is within the guidelines suggested by European Food Safety Authority. Although this fortification darkened the crumb and increased crumb and crust springiness and had impact on volatile profile, concerning key odours only hexanal presented a significant increase in fortified bread. Two machine types (with 1 or 2 paddles) were tested but had a minor impact on bread characteristics. Descriptive analyses performed by a trained panel showed no significant differences in sensorial attributes. Dry spent yeast can be used as ingredient in home-made bread to increase β-glucan intake, and contribute to valorisation of this brewing by-product.